2015
DOI: 10.1002/2014wr015767
|View full text |Cite
|
Sign up to set email alerts
|

On the upscaling of mass transfer rate expressions for interpretation of source zone partitioning tracer tests

Abstract: Analysis of partitioning tracer tests conducted in dense nonaqueous phase liquid (DNAPL) source zones relies on conceptual models that describe mass exchange between the DNAPL and aqueous phases. Such analysis, however, is complicated by the complex distribution of entrapped DNAPL mass and formation heterogeneity. Due to parameter uncertainty in heterogeneous regions and the desire to reduce model complexity, the effect of mass transfer limitations is often neglected, and an equilibrium-based model is typic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 42 publications
(107 reference statements)
0
7
0
Order By: Relevance
“…Distributions of non‐wetting fluid saturations are often quantified using spatial moments, in both experiments and numerical simulations (Kueper and Frind, 1991; Essaid and Hess, 1993; Kueper and Gerhard, 1995; Lemke et al, 2004; Christ et al, 2005; Fagerlund et al, 2007; Pantazidou and Liu, 2008; Boroumand and Abriola, 2015). For a porous medium containing water and gas, the spatial moments in two dimensions are defined as Mij=i=j=θnormalρgSg(x,z)xizjdxdz where θ is the porosity, ρ g is the gas density, S g is the gas saturation, and x and z are the horizontal and vertical positions in a two‐dimensional domain.…”
Section: Introductionmentioning
confidence: 99%
“…Distributions of non‐wetting fluid saturations are often quantified using spatial moments, in both experiments and numerical simulations (Kueper and Frind, 1991; Essaid and Hess, 1993; Kueper and Gerhard, 1995; Lemke et al, 2004; Christ et al, 2005; Fagerlund et al, 2007; Pantazidou and Liu, 2008; Boroumand and Abriola, 2015). For a porous medium containing water and gas, the spatial moments in two dimensions are defined as Mij=i=j=θnormalρgSg(x,z)xizjdxdz where θ is the porosity, ρ g is the gas density, S g is the gas saturation, and x and z are the horizontal and vertical positions in a two‐dimensional domain.…”
Section: Introductionmentioning
confidence: 99%
“…Partitioning tracer tests are most successfully applied to identify DNAPL residual saturation, although Moreno‐Barbero and Illangasekare [] have shown that incorporating nonequilibrium partitioning can improve results for high‐saturation zones. Inverse modeling has been successfully used to identify the location and dimensions of a single‐component DNAPL pool within a saturated, steady flow field based on observed downgradient aqueous concentrations [ Sciortino et al ., ], however, determining residual saturations in heterogeneous systems is more challenging [ Boroumand and Abriola , ]. Yeh and Zhu [] combined multiwell hydraulic tomography and partitioning tracer tomography to facilitate analysis in heterogeneous settings.…”
Section: The Organic Napl Sourcementioning
confidence: 99%
“…Indirect, nondestructive methods for evaluating field saturations have been developed to overcome the challenges of direct measurement. Partitioning tracer methods are based on comparing the arrival times in interwell or push-pull tests for multiple tracers with different NAPL partitioning rates [Datta- Gupta et al, 2002;Dugan et al, 2003;Huang et al, 2010;James et al, 1997James et al, , 2000Jawitz et al, 2003;Jin et al, 1995;Moreno-Barbero and Illangasekare, 2006;Zhang and Graham, 2001a,b] [Boroumand and Abriola, 2015]. Yeh and Zhu [2007] combined multiwell hydraulic tomography and partitioning tracer tomography to facilitate analysis in heterogeneous settings.…”
Section: Field Studies Of Napl Flow and Entrapmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past two decades, several different types of simple, upscaled models have been developed and tested, such as equilibrium streamtube methods, power law relationships between concentration and mass, dual-domain models, and other methods with upscaled effective mass transfer rate coefficients (Parker and Park, 2004;Jawitz et al, 2005;Marble et al, 2008;Christ et al, 2010;DiFilippo and Brusseau, 2011a;Boroumand and Abriola, 2015). However, most of these models (e.g., Parker and Park, 2004;Jawitz et al 2005;Basu et al, 2008;Marble et al, 2008;Luciano et al, 2018) produce smooth singular dissolution profiles and thus are not able to capture non-singular dissolution behavior caused by the complexity of the source zone architectures.…”
Section: Introductionmentioning
confidence: 99%